Oxford Studies in Philosophy of Religion 2016
DOI: 10.1093/acprof:oso/9780198757702.003.0007
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Intrinsics and Christological Predication

Abstract: This is a penultimate manuscript, and not a final version, of a forthcoming article in Oxford Studies in Philosophy of Religion. As such, please do not cite this version; cite the official version, due out in OSPR VII in 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…30 ENDNOTES 1 For other discussions of this objection, see: Adams (2006), Arendzen (1941, Bäck (1998, 84), Bartel (1995, Cupitt (1977, 136), Davis (2006, 116), Dawson (2004, 161-162), Evans (2006, 13), Feenstra (2006, 142-144), Ferrier (1962, Geisler and Watkins (1985), Gorman (2000Gorman ( , 2011Gorman ( , 2014Gorman ( , 2016, Hall (1898, chap. 3, section 5;chapter 8), Hebblethwaite (2008, 60), Hick (1989, Hill (2012, Kelly (1994), Knox (1967, 36), Leftow (2011a, 316), Loke (2009, Macquarrie (1990, Moreland and Craig (2003, 597), Morris (1987, Moulder (1986, Pannenberg (1968, 296-297), Pawl (2014a, 2016a, 2016b, Pollard (1955, Senor (2002, 221), Spence (2008, 16), Stump (1989, Sturch (1991, Vallicella (2002), van Inwagen (1998, Ware (2013, 16), and Weston (1914, 181).…”
Section: Discussionmentioning
confidence: 99%
“…30 ENDNOTES 1 For other discussions of this objection, see: Adams (2006), Arendzen (1941, Bäck (1998, 84), Bartel (1995, Cupitt (1977, 136), Davis (2006, 116), Dawson (2004, 161-162), Evans (2006, 13), Feenstra (2006, 142-144), Ferrier (1962, Geisler and Watkins (1985), Gorman (2000Gorman ( , 2011Gorman ( , 2014Gorman ( , 2016, Hall (1898, chap. 3, section 5;chapter 8), Hebblethwaite (2008, 60), Hick (1989, Hill (2012, Kelly (1994), Knox (1967, 36), Leftow (2011a, 316), Loke (2009, Macquarrie (1990, Moreland and Craig (2003, 597), Morris (1987, Moulder (1986, Pannenberg (1968, 296-297), Pawl (2014a, 2016a, 2016b, Pollard (1955, Senor (2002, 221), Spence (2008, 16), Stump (1989, Sturch (1991, Vallicella (2002), van Inwagen (1998, Ware (2013, 16), and Weston (1914, 181).…”
Section: Discussionmentioning
confidence: 99%
“…And in fact, kenotic theologians can respond to Type-C objections to perfect being theology in virtue of certain divine attributes being temporally indexed. Pawl has shown that kenotic theology also has the resources to avoid the logical objection to the Incarnation by insisting on the irreducibility of tense in the copulas joining certain predicates to the Second Person (Pawl 2016). The kenotic theologian ought to say, according to Pawl, that the Second Person was impassible and is passible, and that from this conjunction we cannot derive the logical contradiction that the Second Person is both impassible and passible (Pawl 2016, p. 177).…”
Section: Incarnation Evil Scripturementioning
confidence: 99%
“…As always with such contextual matters, precise rules are not available. Pawl (2015) classifies 'qua'-based responses to the apparent Christological contradictions on the basis of the role played by the term 'qua': it could signal tense, signal a tacit sortal, or modify the subject, predicate or copula. Perhaps surprisingly it is not quite clear how the above account fits into Pawl's classification.…”
Section: Metaphysical Truth Conditionsmentioning
confidence: 99%
“…Finally, I will discuss the possibility of extending the story outside of the nested mode context, and how one might reconcile the account with divine simplicity. 1 1 For an excellent thorough recent discussion of the ways of understanding the Christological 'qua' , see Pawl (2015).…”
Section: Introductionmentioning
confidence: 99%